The role of mNGS in the diagnosis of talaromycosis and case series - Jing Zhao; Hui-Ting Su; Dong Zhang; Xue-Tong Li; Min-Ya Lu; Juan Du; Jia-Yu Guo; Yi Gao; Xin-Fei Chen; Dong-Hua Wen; Shi-Yu Jia; Yao Wang; et al. (BMC Infectious Diseases, 2025)
Abstract Background Talaromycosis is a rare fungal infection characterized by non-specific clinical features, often resulting in misdiagnosis. This study aimed to analyze four classic cases of Talaromyces marneffei infection diagnosed using metagenomic next-generation sequencing (mNGS) to improve understanding of its diagnosis and treatment. Methods This study retrospectively analyzed cases of T. marneffei identified through mNGS at Peking Union Medical College Hospital. Four confirmed cases of talaromycosis were selected based on clinical diagnoses, supplemented by a review of relevant literature. We reviewed and compared the clinical features, laboratory indicators, treatment regimens, and outcomes of these cases, which exhibited varied characteristics. Results Among the four patients, two were human immunodeficiency virus (HIV)-positive, and two were HIV-negative. All the participants presented with fever and varying respiratory symptoms, with distinct clinical characteristics aiding diagnosis. Three cases exhibited significant pulmonary infection lesions. Both HIV-positive patients showed T. marneffei bloodstream dissemination and suffered mixed infection with virus. Within them, one case was positive in blood culture, blood mNGS and sputum culture. Another case was positive in blood and bone marrow cultures, brain tissue culture and mNGS. They were both treated with voriconazole and improved. Both HIV-negative patients were T. marneffei positive for BALF mNGS, and only one of them was positive for BALF culture. One of them was mix infected by fungi, bacteria, Mycobacterium tuberculosis and virus, improved by voriconzole and followed by introconaole. The other case was cured by introconazole. Conclusions Traditional diagnostic methods are limited by factors such as the long time and low sensitivity of fungal culture, the effect of prior antibiotic treatment, the invasiveness and complexities of tissue biopsies, and so on. Emerging technologies, particularly mNGS, offer advantages such as rapid processing, high accuracy, and comprehensive pathogen coverage, significantly reducing the risk of missed diagnoses and facilitating timely intervention.